Ultrahigh-strength concrete and preparation method thereof
By using specific combinations of external admixtures in concrete, the problem of traditional C80 concrete being susceptible to carbonization reactions in humid environments in the south is solved, which significantly improves the carbonization resistance and durability of concrete, and meets the high-performance concrete of modern buildings. need.
Patent Information
- Application Number
- CN202411596557.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional C80 concrete is susceptible to carbonization in humid environments in the south, resulting in accelerated corrosion and cannot meet the demand for high-performance concrete in modern buildings.
The external dopant composed of polycarboxylic acid water reducer, bidodecyldimethylammonium bromide, sodium tripolyphosphate and cetaceous alcohol polyoxyethylene ether is significantly improved Concrete's carbonization resistance and durability.
The concrete has significantly improved its carbonization resistance and durability, allowing it to show better mechanical properties and extend its building service life in humid environments in the south.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete, and in particular to ultra-high strength concrete and a preparation method thereof. Background Art
[0002] High-performance concrete has good working performance and mechanical properties, conforms to the development trend of modern architecture, and is widely used in modern construction projects, especially in structures that need to bear huge loads, such as high-rise buildings, bridges, and large-span structures. C80 concrete is one of the common high-performance concretes, with high compressive strength and durability. However, with the continuous development of modern construction technology, the performance requirements for concrete are getting higher and higher, and traditional C80 concrete can no longer fully meet the needs of certain specific projects. Especially in the humid environment of the south, concrete is very easy to react chemically with moisture and carbon dioxide in the air, accelerating the carbonization reaction of concrete, thereby accelerating the corrosion rate of concrete, and even weakening the protective effect of concrete on steel bars, accelerating the rust of steel bars, and shortening the service life of buildings. Therefore, there is an urgent need for a C80 concrete that can have good anti-carbonation performance in the humid environment of the south. Summary of the invention
[0003] In order to obtain a C80 concrete with good anti-carbonation performance in the humid environment of the south, the present application provides an ultra-high strength concrete and a preparation method thereof. The ultra-high strength concrete provided by the present application, by adding an admixture composed of a polycarboxylic acid water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate and cetyl stearyl alcohol polyoxyethylene ether, can not only meet the needs of modern construction projects for high-performance concrete, but also is particularly suitable for the humid environment of the south, has good durability, and can significantly extend the service life of the building.
[0004] In the first aspect, the ultra-high strength concrete provided in the present application adopts the following technical solution: A super-high strength concrete comprises the following components in parts by weight: 400-460 parts of cement, 575-670 parts of sand, 980-1138 parts of stone, 115-135 parts of water, 149-178 parts of mixed admixtures, and 16.56-19.3 parts of admixtures; the admixtures are composed of a polycarboxylic acid water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate and cetearyl alcohol polyoxyethylene ether.
[0005] In the above technical scheme, the present application significantly improves the carbonation resistance of concrete, and significantly improves the mechanical properties and durability of concrete by reasonably selecting and proportioning the various components in concrete, especially by introducing an admixture composed of a polycarboxylic acid water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate and cetearyl alcohol polyoxyethylene ether. The polycarboxylic acid water reducer can effectively reduce the water-cement ratio of concrete and improve the working performance of concrete; the antibacterial property of didodecyl dimethyl ammonium bromide can further improve the durability of concrete and further extend the service life of the building by improving the antibacterial property of concrete, avoiding the growth of microorganisms on the surface of concrete, and reducing the corrosion of microorganisms to concrete; sodium tripolyphosphate can delay the setting time of concrete, thereby promoting the full hydration of concrete and obtaining concrete with higher density; cetearyl alcohol polyoxyethylene ether helps to improve the dispersibility and fluidity of the various components in concrete, thereby further improving the uniformity and density of concrete. At the same time, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate and cetearyl alcohol polyoxyethylene ether have a synergistic effect. By changing the charge distribution on the surface of concrete, they improve the surface wettability and permeability of concrete, which not only enhances the concrete's ability to repel harmful ions, but also enables didodecyl dimethyl ammonium bromide, sodium tripolyphosphate and cetearyl alcohol polyoxyethylene ether to be more evenly dispersed in the concrete, further promoting the full hydration of the concrete, further improving the density and impermeability of the concrete, thereby further improving the concrete's anti-carbonation performance and further improving the durability of the concrete.
[0006] Preferably, based on the weight of the ultra-high strength concrete, the admixture includes 9.6 to 10.9 parts of polycarboxylic acid water reducer, 2.43 to 2.9 parts of didodecyl dimethyl ammonium bromide, 2.89 to 3.51 parts of sodium tripolyphosphate and 1.64 to 1.95 parts of cetearyl alcohol polyoxyethylene ether.
[0007] In the above technical scheme, the present application ensures that the prepared concrete has good mechanical properties and durability by limiting the dosage of polycarboxylic acid type water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate and cetearyl alcohol polyoxyethylene ether.
[0008] Preferably, the weight ratio of the polycarboxylic acid water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate and cetearyl alcohol polyoxyethylene ether is 10.1:2.78:3.24:1.81.
[0009] In the above technical scheme, this application limits the weight ratio of polycarboxylic acid water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate and cetearyl alcohol polyoxyethylene ether to 10.1:2.78:3.24:1.81, so that the performance of concrete is optimally balanced, and the mechanical properties and durability of concrete are further optimized.
[0010] Preferably, the mixed external admixtures include fly ash, mineral powder and silica fume; based on the weight of the ultra-high strength concrete, the mixed external admixtures include 63 to 77 parts of fly ash, 65 to 74 parts of mineral powder and 21 to 27 parts of silica fume.
[0011] In the above technical scheme, the present application further optimizes the mechanical properties and durability of concrete by selecting fly ash, mineral powder and silica fume as mixed admixtures. The addition of fly ash and mineral powder can effectively reduce the amount of cement, thereby reducing the heat release of concrete, reducing the occurrence of shrinkage cracks, and improving its durability. The addition of silica fume can significantly improve the early and late strength of concrete, and at the same time, the capillary pores of concrete are blocked by the action of micro-aggregates, further enhancing its impermeability. In addition, the combined use of fly ash, mineral powder and silica fume can make the internal structure of concrete denser, thereby improving the anti-carbonation performance of concrete.
[0012] Preferably, the weight ratio of fly ash, mineral powder and silica ash is 70:70:25.
[0013] In the above technical solution, by limiting the weight ratio of fly ash, mineral powder and silica fume to 70:70:25, this specific weight ratio can ensure the optimal synergistic effect between fly ash, mineral powder and silica fume, thereby further optimizing the compaction resistance and carbonization resistance of concrete, and further optimizing the mechanical properties and durability of concrete.
[0014] Preferably, 2.28 to 2.76 parts of steel fibers are also included.
[0015] In the above technical solution, the present application significantly improves the crack resistance and impact resistance of concrete by further adding steel fibers to concrete, thereby significantly improving the mechanical properties of concrete. Steel fibers are evenly distributed in concrete and can effectively bridge microcracks, thereby improving the toughness of concrete and reducing the generation and expansion of cracks. When subjected to external loads, steel fibers can absorb and disperse stress, improve the bearing capacity of concrete, and thus extend the service life of the building.
[0016] Preferably, the sand refers to machine-made sand with a fineness modulus of 2.7, and the stone refers to continuous grade crushed stone with a particle size of 10 to 16 mm.
[0017] In the above technical solution, by using crushed stone with a specific particle size range and machine-made sand with a fineness modulus, the structure of concrete can be further optimized and its mechanical properties and durability can be improved. Machine-made sand contains an appropriate amount of stone powder relative to river sand, which can improve the density of concrete through micro-aggregate filling, further improve the concrete's impermeability, and further improve the durability of concrete. Strictly controlling the particle size of crushed stone to 10 to 16 mm can ensure the uniformity of the internal structure of concrete, reduce the strength difference caused by uneven particle size, and thus improve the overall performance of concrete.
[0018] In a second aspect, the present application provides a method for preparing ultra-high strength concrete using the following technical solution: A method for preparing ultra-high strength concrete comprises the following steps: Step 1: Mix cement, sand, stone and mixed admixtures evenly to obtain a dry mix; mix polycarboxylic acid water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate, cetearyl alcohol polyoxyethylene ether with water, and stir evenly to form an admixture solution; Step 2: add the admixture solution to the dry mix, continue stirring until it is evenly mixed, and obtain ultra-high strength concrete.
[0019] In the above technical scheme, the present application ensures the uniformity and stability of concrete by premixing the dry mix and the admixture solution through the above preparation method, so as to avoid uneven strength or stratification of concrete during use, and ensures that the ultra-high strength concrete can give full play to the best mechanical properties and durability during use. The ultra-high strength concrete prepared in this way not only meets the demand for high-performance concrete in modern construction projects, but is also particularly suitable for the humid environment in the south, and can effectively extend the service life of the building.
[0020] Preferably, step 1 is as follows: cement, sand, stone, mixed admixtures and steel fiber are mixed evenly to obtain a dry mix; polycarboxylic acid water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate, cetearyl alcohol polyoxyethylene ether are mixed with water, and stirred evenly to form an admixture solution.
[0021] In the above technical solution, the application further improves the tensile strength and crack resistance of concrete by adding steel fibers, so that concrete can show better mechanical properties under heavy loads and complex stress conditions. At the same time, steel fibers form a three-dimensional network structure inside the concrete, which can effectively bridge microcracks, thereby inhibiting the expansion of cracks and improving the durability of concrete.
[0022] In summary, the present application includes at least one of the following beneficial technical effects: 1. The present application reduces the water-cement ratio of concrete, improves the working performance of concrete, and reduces temperature cracks of concrete by adding a polycarboxylic acid-type water-reducing agent to concrete. Through the synergistic effect of didodecyl dimethyl ammonium bromide, sodium tripolyphosphate, and cetearyl alcohol polyoxyethylene ether, the carbonization resistance of concrete is significantly improved, and the mechanical properties and durability of concrete are significantly improved, thereby meeting the needs of modern construction projects for high-performance concrete, especially meeting the needs of construction projects for high-performance concrete in the humid environment of the south.
[0023] 2. This application further improves the tensile strength and crack resistance of concrete by further adding steel fibers to concrete, so that the concrete can exhibit better mechanical properties under heavy loads and complex stress conditions, significantly improving the mechanical properties and durability of concrete. DETAILED DESCRIPTION
[0024] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0025] Example 1 An ultra-high strength concrete comprises 430 kg of cement, 625 kg of sand, 1060 kg of stone, 125 kg of water, 70 kg of fly ash, 70 kg of mineral powder, 25 kg of silica fume, 10.1 kg of polycarboxylic acid type water reducing agent, 2.78 kg of didodecyl dimethyl ammonium bromide, 3.24 kg of sodium tripolyphosphate, 1.81 kg of cetearyl alcohol polyoxyethylene ether and 2.53 kg of steel fiber.
[0026] Among them, the cement is P.‖52.5 cement, purchased from Yingde Conch Cement Co., Ltd.
[0027] Among them, the sand is machine-made sand with a fineness modulus of 2.7, purchased from Guangzhou Shunxing Stone Quarry Co., Ltd.
[0028] Among them, the stone is a continuous grade crushed stone with a particle size of 10 to 16 mm.
[0029] Among them, the fly ash is secondary fly ash.
[0030] Among them, the mineral powder is S95 grade mineral powder.
[0031] Among them, silica fume was purchased from Yongshun Mineral Products Processing Plant in Lingshou County, mesh number: 1250.
[0032] Among them, the polycarboxylic acid water reducer was purchased from Guangzhou Huayang Chemical Co., Ltd., model: SPEG TPEG.
[0033] Among them, didodecyl dimethyl ammonium bromide was purchased from Tesco Chemical (Hubei) Co., Ltd.
[0034] Among them, sodium tripolyphosphate was purchased from Guangdong Zhonghan Chemical Co., Ltd., item number: 2010790704201.
[0035] Among them, cetearyl alcohol polyoxyethylene ether was purchased from Guangzhou Shanghe Chemical Technology Co., Ltd. with the trade name: cetearyl alcohol polyether-25.
[0036] Among them, the steel fiber was purchased from Guangxi Nanning Sanzheng Engineering Materials Co., Ltd., item number: hh89394256.
[0037] The method for preparing ultra-high strength concrete comprises the following steps: Step 1: Mix cement, sand, stone, fly ash, mineral powder, silica fume and steel fiber evenly to obtain a dry mix; mix polycarboxylic acid water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate, cetearyl alcohol polyoxyethylene ether with water, and stir evenly to form an external admixture solution.
[0038] Step 2: Add the admixture solution into the dry mix and continue stirring until the mixture is uniform to obtain ultra-high strength concrete.
[0039] Example 2 An ultra-high strength concrete, which is different from Example 1 in that it includes 400kg of cement, 575kg of sand, 980kg of stone, 115kg of water, 63kg of fly ash, 65kg of mineral powder, 21kg of silica fume, 9.6kg of polycarboxylic acid type water reducer, 2.43kg of didodecyl dimethyl ammonium bromide, 2.98kg of sodium tripolyphosphate, 1.64kg of cetearyl alcohol polyoxyethylene ether and 2.28kg of steel fiber.
[0040] The method for preparing ultra-high strength concrete comprises the following steps: Step 1: Mix cement, sand, stone, fly ash, mineral powder, silica fume and steel fiber evenly to obtain a dry mix; mix polycarboxylic acid water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate, cetearyl alcohol polyoxyethylene ether with water, and stir evenly to form an external admixture solution.
[0041] Step 2: Add the admixture solution into the dry mix and continue stirring until the mixture is uniform to obtain ultra-high strength concrete.
[0042] Example 3 An ultra-high strength concrete, which is different from Example 1 in that it includes 460kg of cement, 670kg of sand, 1138kg of stone, 135kg of water, 77kg of fly ash, 74kg of mineral powder, 27kg of silica fume, 10.9kg of polycarboxylic acid water reducer, 2.9kg of didodecyl dimethyl ammonium bromide, 3.51kg of sodium tripolyphosphate, 1.95kg of cetearyl alcohol polyoxyethylene ether and 2.76kg of steel fiber.
[0043] The method for preparing ultra-high strength concrete comprises the following steps: Step 1: Mix cement, sand, stone, fly ash, mineral powder, silica fume and steel fiber evenly to obtain a dry mix; mix polycarboxylic acid water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate, cetearyl alcohol polyoxyethylene ether with water, and stir evenly to form an external admixture solution.
[0044] Step 2: Add the admixture solution into the dry mix and continue stirring until the mixture is uniform to obtain ultra-high strength concrete.
[0045] Example 4 An ultra-high strength concrete, which is different from Example 1 in that an equal amount of silica fume is replaced by limestone powder.
[0046] Example 5 An ultra-high strength concrete, which is different from the embodiment 1 in that it does not contain steel fibers.
[0047] The method for preparing ultra-high strength concrete comprises the following steps: Step 1: Mix cement, sand, stone, fly ash, mineral powder and silica fume evenly to obtain a dry mix; mix polycarboxylic acid water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate, cetearyl alcohol polyoxyethylene ether with water, and stir evenly to form an external admixture solution.
[0048] Step 2: Add the admixture solution into the dry mix and continue stirring until the mixture is uniform to obtain ultra-high strength concrete.
[0049] Comparative Example 1 An ultra-high strength concrete, which is different from Example 1 in that didodecyl dimethyl ammonium bromide is replaced by hexadecyl trimethyl ammonium bromide in equal amounts.
[0050] Comparative Example 2 An ultra-high strength concrete, which is different from Example 1 in that sodium tripolyphosphate is replaced by sodium hexametaphosphate in equal amounts.
[0051] Comparative Example 3 A super high strength concrete, which is different from Example 1 in that cetearyl alcohol polyoxyethylene ether is replaced by lauryl alcohol polyoxyethylene ether in an equal amount.
[0052] Performance Testing According to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the compressive strength and flexural strength of concrete after standard curing for 28 days were tested.
[0053] According to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the carbonation depth (carbonation 28d) and electrical flux of standard 28d concrete were tested.
[0054] The above test results are shown in Table 1.
[0055] Table 1: Test items Compressive strength / MPa Flexural strength / MPa Carbonization depth / mm Electric flux / C Example 1 59.1 7.9 1.03 789 Example 2 58.3 7.5 1.09 804 Example 3 58.8 7.8 1.05 792 Example 4 56.9 7.3 1.13 937 Example 5 55.7 6.9 1.21 1014 Comparative Example 1 53.3 6.7 4.06 2168 Comparative Example 2 52.4 6.4 4.87 2551 Comparative Example 3 52.9 6.6 4.32 2374 Specifically combined with the analysis of Examples 1-5 and Comparative Examples 1-3, it can be concluded that the ultra-high strength concrete prepared in the examples of the present application has good compressive strength, flexural strength, carbonization resistance and chloride ion penetration resistance, that is, the ultra-high strength concrete prepared in the examples of the present application has good mechanical properties and durability.
[0056] Specifically analyzing in combination with Example 1 and Comparative Examples 1-3, the difference between Comparative Examples 1-3 and Example 1 is that Comparative Examples 1-3 respectively replace didodecyl dimethyl ammonium bromide, sodium tripolyphosphate and cetearyl alcohol polyoxyethylene ether, and Example 1 has good mechanical properties and durability. It can be seen that in the present application, the selection of didodecyl dimethyl ammonium bromide, sodium tripolyphosphate and cetearyl alcohol polyoxyethylene ether is particular. The three have a synergistic effect and can work together on concrete to promote full hydration of concrete, improve the density and impermeability of concrete, improve the carbonization resistance of concrete, and improve the durability of concrete.
[0057] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An ultra-high strength concrete, characterized in that: The invention comprises the following components in parts by weight: 400-460 parts of cement, 575-670 parts of sand, 980-1138 parts of stone, 115-135 parts of water, 149-178 parts of mixed admixtures, and 16.56-19.3 parts of admixtures; the admixtures are composed of a polycarboxylic acid water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate and cetearyl alcohol polyoxyethylene ether.
2. The ultra-high strength concrete according to claim 1, characterized in that: Calculated by weight of the ultra-high strength concrete, the admixture includes 9.6-10.9 parts of polycarboxylic acid water reducer, 2.43-2.9 parts of didodecyl dimethyl ammonium bromide, 2.89-3.51 parts of sodium tripolyphosphate and 1.64-1.95 parts of cetearyl alcohol polyoxyethylene ether.
3. The ultra-high strength concrete according to claim 1, characterized in that: The weight ratio of the polycarboxylic acid water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate and cetearyl alcohol polyoxyethylene ether is 10.1:2.78:3.24:1.
81.
4. The ultra-high strength concrete according to claim 1, characterized in that: The mixed external admixtures include fly ash, mineral powder and silica fume; based on the weight of the ultra-high strength concrete, the mixed external admixtures include 63-77 parts of fly ash, 65-74 parts of mineral powder and 21-27 parts of silica fume.
5. The ultra-high strength concrete according to claim 4, characterized in that: The weight ratio of the fly ash, mineral powder and silica ash is 70:70:
25.
6. The ultra-high strength concrete according to claim 1, characterized in that: It also includes 2.28 to 2.76 parts of steel fibers.
7. The ultra-high strength concrete according to claim 1, characterized in that: The sand refers to machine-made sand with a fineness modulus of 2.7, and the stone refers to continuous grade crushed stone with a particle size of 10 to 16 mm.
8. A method for preparing ultra-high strength concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Mix cement, sand, stone and mixed admixtures evenly to obtain a dry mix; Mixing polycarboxylic acid water reducing agent, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate, cetearyl alcohol polyoxyethylene ether and water, and stirring evenly to form an external admixture solution; Step 2: Add the admixture solution into the dry mix and continue stirring until the mixture is uniform to obtain ultra-high strength concrete.
9. The method for preparing ultra-high strength concrete according to claim 8, characterized in that: The step 1 is as follows: The cement, sand, stone, mixed admixture and steel fiber are mixed evenly to obtain a dry mix; the polycarboxylic acid water reducer, didodecyl dimethyl ammonium bromide, sodium tripolyphosphate, cetearyl alcohol polyoxyethylene ether are mixed with water, and stirred evenly to form an admixture solution.